PENGARUH PENERAPAN MODEL PEMBELAJARAN ASSURE BERBANTUAN MEDIA VIDEO TERHADAP HASIL BELAJAR PADA MATERI KESETIMBANGAN KIMIA SISWA XI IPA SMA NEGERI 4 PULAU MOROTAI - Mujamin Lasaari; Zulkifli Zam Zam; Nurfatimah Sugra (Universitas Khairun, 2019)
This research was conducted to determine the effect of assurelearning model based onvideo media towards chemical equilibrium materials result of XI IPA students in SMANegeri 4 Morotai Island. The research typewas experimental research using pretest-posttest control group design. The population was XI IPA students at SMA Negeri 4 Morotai Island in 2nd semester academic year 2017/2018 and the total numbers were 48 students consist of two classes. Thetechnique sampling used saturated sampling technique. The instruments were 10 items essay questions to measure students’ learning result while observation sheets for assesing affective and psychomotor domain. Data analyzed used t-test. The results showed that there was an effect on the learning results of XI IPA students in SMA Negeri 4 Morotai Island on chemical equilibrium material based on the results of the t-test obtained thisis 4.81>ttabis 2,000 with the increasing of 2.34%.Keywords: video,media, assurelearning model, students result.